Variables controlling elicitation and suppression of subvocal defence mechanism - MacCann Haslett, D. (Economic & Social Studies, 1975)
A persuasive, counter-attitudinal communication was individually delivered to 66 male respondents. While the baseline control group (N = 12) merely received the message, the 54 experimental subjects responded to concurrently distracting stimuli by performing visual, vocal or manual tasks. The results obtained suggest that those tasks which involve the participant in an active rather than a passive response are more likely to suppress the subvocal defensive process of counter-argumentation, as measured by a modification of Brock's (1967) procedure.
Keywords: Brock's mechanism; Participant engagement - Research